Structural equation modeling for exploring the barriers to accessing healthcare among hijra in Bangladesh - Mohammad Niaz Morshed Khan; Michiko Moriyama; Md. Enamul Haque; Syeda Naushin Parnini; Mohammad Abul Bashar Sarker; Shadat Hossain; Md. Masud Reza; Samira Dishti Irfan; Shehrin Shaila Mahmood; Gail Knudson; Sharful Islam Khan (PLoS ONE, 2026)
Introduction Hijra in Bangladesh and other South Asian countries face considerable barriers to healthcare given their potential exposure to repeated, multi-level stigmatization and marginalization. However, these needs remain unaddressed in the healthcare system, thus warranting exploration of their healthcare access barriers. This article examines healthcare access barriers among hijra in Bangladesh. Methods A cross-sectional survey was conducted from June to November 2021 among 544 hijra across 16 districts out of 64 districts (25%) across all eight divisions in Bangladesh using multi-stage stratified cluster sampling, thus spanning a wide geographical coverage. Among all the participants, those who reported health problems in the last six months and sought treatment as a hijra (N = 215) were further used for analysis. Structural equation modeling (SEM) was utilized to assess and quantify the pathways how harassment, financial difficulties, discrimination, fear of discrimination, and lack of infrastructural facilities significantly creates barriers in accessing healthcare facilities among hijra . The results were expressed using factor loadings (FL) where FL closer to 1 indicated strong relationship. Results The average age of hijra participants was 32 years old (±10.3 SD). The participants reported an average monthly income of US$107.2. Findings revealed that 53.5% of hijra respondents encountered four types of healthcare access barriers: harassment, discrimination, financial difficulties, and lack of infrastructural facilities in some form. Among these healthcare access barriers, our model illustrated that three were significant. These were discrimination by healthcare providers (Factor Loading = 1.14), which was the most significant barrier, followed by harassment by healthcare providers (Factor Loading = 0.93) and lack of infrastructural facilities (Factor loading = 0.41), and all these three barriers lead to an ultimate barrier to access to healthcare for the hijra community. Conclusion This study highlights the critical barriers faced by hijra in accessing healthcare in Bangladesh. Findings suggest that interventions aimed at improving healthcare access should simultaneously address multiple factors to ensure gender-responsive healthcare systems that do not conform to a rigid gender binary.